Systematic review and meta-analysis of internal jugular vein variants and their relationship to clinical implications in the head and neck - Nova Baeza, Pablo.; Valenzuela Fuenzalida, Juan José.; Valdivia Arroyo, Rocío.; Becerra Rodríguez, Emelyn Sofia.; Escalona Manzo, Catalina.; Castaño Gallego, Yesica Tatiana.; Luque Bernal, Ricardo Miguel.; Oyanedel Amaro, Gustavo.; Suazo Santibáñez, Alejandra Isabel.; Orellana Donoso, Mathias Ignacio.; Bruna Mejías, Alejandro.; Sanchis Gimeno, Juan A.; et al. (MDPI, 2024)
Background: The internal jugular vein (IJV) is a vascular structure that is responsible for the venous drainage of both the head and neck and is commonly found posterior to the internal carotid artery and adjacent to cervical lymph nodes or nerve structures such as the glossopharyngeal and accessory nerves. As a vagal nerve, it is an important reference point for surgical access in neck interventions and dissections. Methods: The databases Medline, Scopus, Web of Science, Google Scholar, CINAHL, and LILACS were searched until August 2024. Methodological quality was evaluated with an assurance tool for anatomical studies (AQUA). Pooled prevalence was estimated using a random effects model. Results: A total of 10 studies met the established selection criteria in this meta-analysis study. The prevalence of variants of the IJV was 3.36% (CI: 2.81–6.96%), with a heterogeneity of 94.46%. Regarding the subgroup analysis, no study presents statistically significant differences in the studies analyzed for this review. Conclusions: Knowing the IJV variants in detail will make early diagnosis useful, especially in surgeries in the neck region and in classic surgeries such as thyroidectomies and tracheostomies, among others. It will be important to know the position of the IJV.
Keywords: Aberrant jugular internal vein; Anatomical variations; Clinical anatomy; Encephalic venous drainage; Jugular internal vein variations